A Study On Gasoline Engine Fuel Octane Numbers Using Accelerometer Analyzing And Statistical Measurement - Ramli, Mohd Irman; Ngatiman, Nor Azazi; Ab Ghani, Ahmad Fuad; Hamzah, Nur Habibah (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
Octane numbers are considered as one of the most important things element in fuel to ensure the performance of the engine. Octane numbers are also can be the cause of failure to the engine. This study is present about the performance of the engine that relates to the octane numbers and compression ratio. The experimental procedure was performed by using three specimen fuels within the specific range of speed at the engine. Data acquisition involved the vibration signal recorded by the accelerometer sensor. The vibration signal that produced by dynamic response of combustion engine has been analyzed using Fast Fourier Transform (FFT). All the data recorded are filtered using the MATLAB to get the valid data. The data obtained from the experiment were analyzed using statistical analysis method to make the interpretation of the data obtained. Mean absolute percentage error and root mean square error has been showing the suitable fuel for the engine N43B20. Correlation process has been proved that it can be used as a standard for determining the suitable fuel for the engine through statistical analysis which is non-destructive, low cost and efficient method.